Utilization of Malaria Diagnostic Tests and Receipt of Anti-Malarial Drugs by Febrile Patients Attending Outpatient Clinics of Health Centre IV Facilities in Mukono District, Uganda - Naigino, Rose; Katamba, Achilles; Babikako, Harriet M.; Mukose, Aggrey (Health, 2014)
Background: Failure to demonstrate the presence of malaria parasites prior to treatment with anti-malarial drugs remains a challenge in Uganda, often resulting into over-prescription of antimalarial drugs to febrile patients suspected of malaria. The aim of this study was to describe the role of utilization of malaria diagnostic tests and associated factors in the receipt of anti-malarial drugs among febrile patients suspected of malaria. Methods: In a cross-sectional study design, client- exit interviews with febrile patients and key-informant interviews with purposively selected health workers were conducted at outpatient clinics of health centre IV facilities in Mukono district. Data entry and analysis were done using EpiData 3.2 and STATA 10 respectively. Data were described using frequency distributions and proportions. Chi square was used in two by two tables, odds ratios as the measure of association and an alpha level of 0.05 was used in all significance tests. Results: Out of 408 respondents, the majority were female (252, 61.8%) and a third of the samples were aged five years and below. The mean age in years was 3.3 with a standard deviation of 2.1. More than half of the respondents (359, 88%) utilized malaria diagnostic tests and about half (241, 59%) received anti-malarial drugs. There were no statistically significant differences between utilizers and non-utilizers in most characteristics except age, history of indoor residual spraying and perceived satisfaction with services at outpatient clinics. Utilizers were 75% less likely to receive anti-malarial drugs than non-utilizers after controlling for age, sex and residence (OR: 0.25, 95%CI: 0.09, 0.66). Frequent power cut-offs as well as limited knowledge on malaria treatment guidelines amongst laboratory personnel were some of the major limitations to microscopic diagnosis of malaria. Conclusion: Utilizers were 75% less likely to receive anti-malarial drugs as opposed to non-utilizers. This implies that increasing utilization of malaria diagnostic tests can reduce the problem of over-prescription of anti-malarial drugs by 75% among those tested for malaria, since anti-malarial drugs would be received by only those with a parasitologically- confirmed diagnosis of malaria. Policy implications: To overcome the problem of overprescription of anti-malarial drugs, there must be a policy that ensures a consistent power supply in all public health laboratories. Training of health workers should encompass all cadres and work-shifts for laboratory personnel should be established to enhance utilization of malaria diagnostic tests especially at night.
Keywords: Malaria Diagnostic Test; Febrile; Malaria Suspect; Utilizers; Receipt of Anti-Malarial Drugs